Collaborative team assessment of secondary school learning - Moreau, André C.; Granger, Nancy; Gingras, Frédérique; Lavoie Vezeau, Cynthia (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
This article presents a praxeological expost facto study with secondary school teachers working in interdisciplinary teams and wanting to improve their learning assessment practices. We specify the factors that helped to sustain new teaching practices one year after the end of a project aimed at implementing collaborative team functioning and highlight success factors for students with literacy difficulties. Data collected with five teachers enabled us to describe a renewed practice of learning assessment, including the use of a coding tool. We discuss issues that may help or hinder the drive for sustainable changes in learning assessment practices and raise avenues for future research. The study contributes an illustration of a learning assessment practice relevant for both teachers and learners.